A Tool for Understanding and Improving Social and Human Factors in Requirements Management in Software Ecosystems - Vieira Junior, Cassiano Medeiros; Gonçalves, Rodrigo Feitosa; Malcher, Paulo; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Requirements management in software ecosystems (SECO) requires cooperation among multiple actors (e.g., keystone, users, and external developers), and the consideration of social and human factors (SHF) is essential in its activities. Problem: Requirements professionals rarely consider SHF in requirements management due to the lack of practical solutions that explicitly help them address these factors. Solution: Based on a rapid review on SHF in requirements engineering, we developed and evaluated a web tool designed to assist professionals understanding and improving SHF while executing requirements management activities, using sentiment analysis as a central feature. IS theory: This study is motivated by socio-technical theory, as the tool addresses the technical and social aspects of requirements management in SECO. The tool was evaluated using the Technology Acceptance Model (TAM) to understand professionals’ perceptions regarding its usefulness and ease of use. Method: We implemented the software solution and conducted a qualitative feasibility study with four requirements professionals working in SECO to evaluate the tool’s effectiveness and usability. Results: The findings indicate that the tool provides professionals with a new perspective for better understanding the SHF that influence requirements management activities in SECO. Contributions and Impact in the IS area: This study contributes with a tool to support requirements management professionals in understanding and improving SHF in SECO. In academia, it contributes to the knowledge of SHF that affects requirements management in SECO. This study also contributes to the Grand Research Challenge “Strengthening the Socio-technical Approach in Information Systems Research”.